Avaliação de desempenho no âmbito da Polícia Federal : uma análise sobre a viabilidade do método 360º - Lima, Luciano Flores de (2019)
Such is the importance of the efficiency principle in public service that in 1998 it was elevated to the constitutional level as part of the Master Plan for the Reform of the State Apparatus (1995), whose fundamental objective was to propose an organic and functional change in the management of the Brazilian State, in order to implant a managerial model to replace the bureaucratic. The problem: the current methodology of performance evaluation of the Federal Police does not predict evaluation of the heads, nor even of the police officers after they reach thirteen years in the career. Objective: Through the present dissertation the concept of management performance evaluation by the 360 ° method and its applicability within the scope of the Federal Police were studied, in search of the valorization of the public servant and the motivation of the individual evaluated in relation to their professional growth, career, their permanence in the Institution, their professional growth, individual success and team success. Theoretical foundation (sources): The methodology used covered not only bibliographic research, but also documentary and field research, as explained in the project. Approach and type of research: This is a qualitative approach, configuring research as descriptive. The author sought to study the best way of applying the 360º evaluation, so that performance evaluation becomes useful and effective, reflecting the closest possible reality, in order to contribute to the realization of the constitutional principle of efficiency in the public service. Instrument and data collection: data collection was carried out based on the information contained in the evaluation charts of the police and administrative career, as well as several other documents and regulations, as well as a pilot project applied in the institution's own sector. Processing of data (analysis and discussion): the results obtained were analyzed and compared statistically with the necessary exemption to define the utility and feasibility of applying the 360º method in the scope of federal police. Main results and conclusions: Taking into account, therefore, the data and results obtained, it is proposed a model of evaluation of managerial performance by the 360° method for the bosses, that is feasible and useful to the Federal Police